2014
DOI: 10.1161/circulationaha.113.006518
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Cause of Death After Percutaneous Coronary Intervention

Abstract: Background-The impact of changing demographics on causes of long-term death after percutaneous coronary intervention (PCI) remains incompletely defined. Methods and Results-We evaluated trends in cause-specific long-term mortality after index PCI performed at a single center from 1991 to 2008. Deaths were ascertained by scheduled prospective surveillance. Cause was determined via telephone interviews, medical records, autopsy reports, and death certificates. Competing-risks analysis of cause-specific mortality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
96
6
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 163 publications
(115 citation statements)
references
References 37 publications
10
96
6
3
Order By: Relevance
“…Recently, Poulin et al have shown that the use of adenosine stress for perfusion imaging is associated with higher risk of death than exercise testing, and this difference in mortality is mainly driven by noncardiac death. The positivity for perfusion criteria was predictive of noncardiac death at univariable, but not multivariable analysis 24. This is different from our findings but can be explained by different patient selection criteria and sample sizes.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Recently, Poulin et al have shown that the use of adenosine stress for perfusion imaging is associated with higher risk of death than exercise testing, and this difference in mortality is mainly driven by noncardiac death. The positivity for perfusion criteria was predictive of noncardiac death at univariable, but not multivariable analysis 24. This is different from our findings but can be explained by different patient selection criteria and sample sizes.…”
Section: Discussioncontrasting
confidence: 99%
“…To our knowledge, there are no studies evaluating the changing trends in causes of death after SE testing, although emerging data from coronary angiography24 or myocardial perfusion stress imaging25 data suggest that the coronary atherosclerotic burden assessed by functional (stress‐induced perfusion defects) or anatomical (CAD by coronary angiography) proxies predict noncardiac and especially cancer death more than cardiac death. Recently, Poulin et al have shown that the use of adenosine stress for perfusion imaging is associated with higher risk of death than exercise testing, and this difference in mortality is mainly driven by noncardiac death.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, with improved recognition and treatment of these conditions, the associated mortality of these ischemic events may be less than in prior eras, and the relative contributions of noncardiovascular causes of death represent a growing proportion of mortality. 26,27 In light of the neutral association with mortality, and the offsetting ischemic benefits and bleeding risks, the decision to continue DAPT beyond what is currently recommended in guidelines should be tailored to the specific anticipated risks for individual patients.…”
Section: Discussionmentioning
confidence: 99%